ANALISIS FAKTOR-FAKTOR KEBERMANFAATAN, KEMUDAHAN DAN KEPERCAYAAN TERHADAP INTENSI PENGGUNAAN APLIKASI UC STUDENT - Om A.I Simeru; Rinabi Tanamal (Business Management Journal, 2020)
The development of technology, especially in the creation of existing applications, causes users to receive the latest information. However, not all information technology is accepted by all parties, due to inconsistency with existing needs. In this research, explain the intention of using the UC Student application where the variables used are the perception of usefulness, perception of ease, trust and quality of information. The research uses the theory of Technology Acceptance Model (TAM) to determine what factors affect the use Of the UC Student application. The instrument used in this research is a questionnaire (angket), which is distributed online to 100 respondents who have used the UC Student application. Data processing by using SPSS obtained result from regression number as follows Y = 1.279 + 0.412 x1 + 0.176 x2 + 0.093 x3 + 0.036 x4, variable perceived usefulness has the greatest influence on intention to use UC Student application, and variable perceived ease of use gives a positive impact on the UC student intention to use application. In this research perceived variable usefulness have a major influence on the Intention to use UC Student Application